ON THE LOMAX-UNIT TEISSIER DISTRIBUTION: PROPERTIES AND ITS APPLICATIONS - Halidu, Lawali; Usman, Umar; Audu, Ahmed (FUDMA JOURNAL OF SCIENCES, 2025)
In this paper, a new modified continuous asymmetric probability distribution Lomax-Unit Teissier distribution (LxUTD) which extends the baseline Unit Teissier (UTD) distribution was developed. However, the new distribution is capable of handling an asymmetric data sets. Some statistical properties like moments, moment generating function, renyi entropy, quantile function, and order statistics was derived and presented theoretically. We also, proceed to test the validity of the new constructed continuous asymmetric probability distribution. A simulation was conducted to determine the efficiency of the estimated value by increasing the sample size. The result shows that when simulated or real life datasets are being used the new asymmetric probability distribution will give better fit than the competitive models.
Keywords: Lomax; Teissier distribution; Asymmetric; Simulation